2013
DOI: 10.1021/jp309225v
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Processing and Characterizations of Dye-Sensitized Solar Cells Based on Nanostructured TiO2

Abstract: This work reports an extensive study about the effects of thermal treatments on the performance of TiO 2based dye-sensitized solar cells. The morphologic, structural, luminescence, and electrical properties of the as-prepared TiO 2 electrode are first analyzed by using several diagnostic techniques. In particular, by extensive cathodoluminescence and photocurrent measurements it is possible to determine the energy band diagram of the material intragap levels and to observe their influence in both radiative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…27,64,65 Therefore PBEx functional seems to be appropriate for the DFT calculation of TiO 2 NP on the basis of the calculated ∆ H-L value. Hence, the structures and data calculated using PBEx are mainly presented for the sake of simplicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,64,65 Therefore PBEx functional seems to be appropriate for the DFT calculation of TiO 2 NP on the basis of the calculated ∆ H-L value. Hence, the structures and data calculated using PBEx are mainly presented for the sake of simplicity.…”
Section: Resultsmentioning
confidence: 99%
“…24 The defect states originating from trapped electrons appear around 1.0 eV below the conduction band minimum (CBM), which induces band gap narrowing as optimal value for photocatalyst. 23,[25][26][27] Herein, we systemically investigate the properties of stoichiometric (TiO 2 ) 35 anatase NP and neutral single oxygen removed one. The bipyramidal (TiO 2 ) 35 NP, maintaining anatase structure after geometrical relaxation, seems to be a proper model to study the physical and electronic properties of oxygen vacancy in TiO 2 NP by comparing those of bulk and slab surface.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the metastability of anatase and the phase difference in the crystal-nucleus-size titania, we have proposed a kinetic control nucleation model from a combinational viewpoint of polymer chemistry and coordination chemistry instead of thermodynamics. The basic understanding of the thermal properties contributes to improving the energy conversion efficiency of DSCs by 10% through the thermal annealing process of TiO 2 nanocrystalline film for better connection between nanocrystals without the phase change and size growth, as recently reported50. Since the phase control is important for nano materials and devices, we still need the further works to understand and control the crystal phase of nanocrystals.…”
Section: Discussionmentioning
confidence: 98%
“…8 In addition, it has been recently found that a mixed anatase/rutile phase exhibits an enhancement of the TiO 2 photocatalytic performance, 9,10 with relevant consequences in the improvement of the production of hydrogen from water or the efficiency of dye-sensitized solar cells. 7 Hence, optimized TiO 2 applicability in this field can be achieved through precise control of the phase composition. In that way, efforts are directed toward the controlled growth of stabilized anatase and rutile single and mixed phases, as well as the understanding of the anatase to rutile transition.…”
Section: ■ Introductionmentioning
confidence: 99%